As rotinas produtivas do telejornalismo na Covid-19: o caso das emissoras da rede globo da Paraíba - Araújo, Mateus Bezerra (2022)
Given the context of the Covid-19 pandemic, it was noticed that the need and demand for information has increased considerably, and the press had to multiply efforts to maintain its coverage, adapting the routines of journalism professionals to suit the recommendations of indicated by the World Health Organization, in order to guarantee the health of its professionals and, consequently, of its sources. Thus, this work aims to identify the main impacts that the Covid-19 pandemic brought to the productive routines of professionals from television stations affiliated with Rede Globo. For this, the present research is based on the Case Study, the Participant Observation and the Oral History, emphasizing the experiences lived by these professionals from the changes brought about by the coronavirus, through semi-structured interviews. As a theoretical contribution, we take as a basis the studies of Traquina (2005), Vizeu (1999), who investigate Journalism; Harvey (1992), which deals with flexible accumulation; and Berger and Luckmann (1985), references in constructivism, among others that investigate professional practices and routines. In the research, we identified clues that indicate changes in work routines in the analyzed TV stations, such as a greater participation of sources in the construction of information and a reality of work practices of greater and more constant challenges and tensions for professional journalists during the pandemic, aimed at large number of fake news, overload of activities and adaptations in content to maintain the productive flow even with health safety protocols.